Case Study Of Forest Conversion Into Palm Oil Land In Indonesia From An Environmental Security View - Juliastica, Febyanti; Akim, Akim; Rezasyah, Teuku (Innovative: Journal Of Social Science Research, 2024)
Abstract In this article, the author discusses the issue of environmental security, which is part of human security. Environmental security is a non-traditional security issue that aims to protect land, water, air, etc. The author limits the case to the issue of forest conversion, often referred to as deforestation, into oil palm land in Indonesia. As we know, environmental problems are still one of the issues that get a lot of attention because the environment that should be able to be used properly is actually damaged or damaged, reducing or even losing the function of the environment itself. Therefore, this article discusses forest conversion that occurs in Indonesia from an environmental security perspective. The results in this article show that there are still people who are affected by the conversion of forests to oil palm land in Indonesia. Keywords: Deforestation, Environmental security, Human Security, Palm oil land.